2021
DOI: 10.15275/rusomj.2021.0309
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Right Ventricular Function To Reveal Cancer Therapy Cardiotoxicity

Abstract: Advances in cancer treatment resulted in augmented patient survival rate. However, anticancer therapy often causes heart damage in the form of a progressive systolic heart failure. Echocardiographic parameters of left ventricular function were conventionally used to detect early manifestations of cancer therapy cardiotoxicity. Improved diagnosing of the right ventricle condition revealed that it is negatively affected by chemotherapy as frequently as the left ventricle, and sometimes even earlier than the latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…4 Evidence has suggested that the RV is affected as frequently as the LV, 4 and even earlier in some situations. 18 To confirm the possibility of assessing the RV to early detect subclinical cardiotoxicity and to define its criteria, larger studies, preferably multicentric ones, are still warranted. 18 CMR and echocardiography are the techniques of choice to evaluate right ventricular systolic function in cancer patients.…”
Section: Anthracyclines and Trastuzumabmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Evidence has suggested that the RV is affected as frequently as the LV, 4 and even earlier in some situations. 18 To confirm the possibility of assessing the RV to early detect subclinical cardiotoxicity and to define its criteria, larger studies, preferably multicentric ones, are still warranted. 18 CMR and echocardiography are the techniques of choice to evaluate right ventricular systolic function in cancer patients.…”
Section: Anthracyclines and Trastuzumabmentioning
confidence: 99%
“…18 To confirm the possibility of assessing the RV to early detect subclinical cardiotoxicity and to define its criteria, larger studies, preferably multicentric ones, are still warranted. 18 CMR and echocardiography are the techniques of choice to evaluate right ventricular systolic function in cancer patients. 16 CMR is the gold standard to assess right ventricular diameter and function.…”
Section: Anthracyclines and Trastuzumabmentioning
confidence: 99%
See 1 more Smart Citation